2017
DOI: 10.1111/pce.12910
|View full text |Cite
|
Sign up to set email alerts
|

Mn accumulation in a submerged plant Egeria densa (Hydrocharitaceae) is mediated by epiphytic bacteria

Abstract: Many aquatic plants act as biosorbents, removing and recovering metals from the environment. To assess the biosorbent activity of Egeria densa, a submerged freshwater macrophyte, plants were collected monthly from a circular drainage area in Lake Biwa basin and the Mn concentrations of the plants were analysed. Mn concentrations in these plants were generally above those of terrestrial hyperaccumulators, and were markedly higher in spring and summer than in autumn. Mn concentrations were much lower in plants i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 49 publications
0
8
1
Order By: Relevance
“…LBB staining and SEM-EDX analysis further indicated that Mn oxides present in the precipitations. A previous study has suggested that the production of biogenic Mn oxides in biofilms on the epidermis of an Mn hyperaccumulator plant, Egeria densa, can elevate Mn levels inside the plants (Tsuji et al 2017). In this study, however, the concentrations of Mn in the leaves, stems, and roots of S. salsa Pall.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…LBB staining and SEM-EDX analysis further indicated that Mn oxides present in the precipitations. A previous study has suggested that the production of biogenic Mn oxides in biofilms on the epidermis of an Mn hyperaccumulator plant, Egeria densa, can elevate Mn levels inside the plants (Tsuji et al 2017). In this study, however, the concentrations of Mn in the leaves, stems, and roots of S. salsa Pall.…”
Section: Discussioncontrasting
confidence: 55%
“…Moreover, the two isolates were clustered together with a short phylogenetic distance and were separated from those above-mentioned marine bacteria. (Tsuji et al 2017). In this work, we observed that when S. salsa Pall.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Biofilter/ biofuel: Azolla filiculoides and A. microphylla are attractive species for the production of renewable biofuels (Miranda et al 2016). Egeria densa can remove heavy metals from the environment (Tsuji et al 2017), as can Eleocharis aciculares, E. macrostachya, and, E. montana (Ha et al 2011, Olmos-Márquez et al 2012. Lemna gibba, L. obscura, L. minuta are indicated for phytoremediation of contaminated water (Gallardo-Williams et al 2002, Gür et al 2016, Di-Baccio et al 2017.…”
Section: Resultsmentioning
confidence: 99%